2022
DOI: 10.1002/mrm.29306
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated dual‐venc 4D flow MRI with variable high‐venc spatial resolution for neurovascular applications

Abstract: Purpose: Dual-velocity encoded (dual-venc or DV) 4D flow MRI achieves wide velocity dynamic range and velocity-to-noise ratio (VNR), enabling accurate neurovascular flow characterization. To reduce scan time, we present interleaved dual-venc 4D Flow with independently prescribed, prospectively undersampled spatial resolution of the high-venc (HV) acquisition: Variable Spatial Resolution Dual Venc (VSRDV).Methods: A prototype VSRDV sequence was developed based on a Cartesian acquisition with eight-point phase e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Neurovascular 4D flow requires high spatiotemporal resolution to detect blood flow in smaller structures 76,77 . Advances in neurovascular 4D flow acquisition, 76–79 reconstruction, 80,81 and the development of postprocessing 82–85 tools have turned 4D flow MRI into a versatile technique for the assessment of CBF dynamics. This includes derivation of a large number of hemodynamic biomarkers (reviewed elsewhere) 67,68,80,84,86–92 .…”
Section: D Csf Flow Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurovascular 4D flow requires high spatiotemporal resolution to detect blood flow in smaller structures 76,77 . Advances in neurovascular 4D flow acquisition, 76–79 reconstruction, 80,81 and the development of postprocessing 82–85 tools have turned 4D flow MRI into a versatile technique for the assessment of CBF dynamics. This includes derivation of a large number of hemodynamic biomarkers (reviewed elsewhere) 67,68,80,84,86–92 .…”
Section: D Csf Flow Imagingmentioning
confidence: 99%
“…A 12.5% scan time reduction can be achieved by sharing a reference scan between the high and low V enc acquisitions 77 . More recently, ~35% scan time reductions in neurovascular dual‐V enc 4D flow scans were demonstrated by undersampling of the high V enc acquisition while preserving the dynamic range and VNRs of dual‐V enc 78 . Other studies have demonstrated the feasibility of accelerating neurovascular 4D flow acquisitions by 25% using machine learning and a convolutional neural network (CNN) that produces three directional velocities from three flow encodings, without requiring a fourth reference scan measuring background phase 81 .…”
Section: D Csf Flow Imagingmentioning
confidence: 99%